2018
DOI: 10.1007/978-3-030-00928-1_68
|View full text |Cite
|
Sign up to set email alerts
|

Joint Correlational and Discriminative Ensemble Classifier Learning for Dementia Stratification Using Shallow Brain Multiplexes

Abstract: The demented brain wiring undergoes several changes with dementia progression. However, in early dementia stages, particularly early mild cognitive impairment (eMCI), these remain challenging to spot. Hence, developing accurate diagnostic techniques for eMCI identification is critical for early intervention to prevent the onset of Alzheimer's Disease (AD). There is a large body of machine-learning based research developed for classifying different brain states (e.g., AD vs MCI). These works can be fundamentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Fourth, all network-based analysis methods overlooked how dementia states affect the relationship between cortical regions in morphology in both stability, conversion, or reversal MCI evolution scenarios. To fill this gap and noting that several studies [27,46] reported that morphological features of the brain, such as cortical thickness, can be affected in neurological disorders, one can use the recently proposed morphological brain networks for dementia diagnosis [47,48,49,50]. Last, none of these works proposed a technique for predicting the full trajectory of brain shape changes as MCI progresses towards AD, remains stable, or reverses to normal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, all network-based analysis methods overlooked how dementia states affect the relationship between cortical regions in morphology in both stability, conversion, or reversal MCI evolution scenarios. To fill this gap and noting that several studies [27,46] reported that morphological features of the brain, such as cortical thickness, can be affected in neurological disorders, one can use the recently proposed morphological brain networks for dementia diagnosis [47,48,49,50]. Last, none of these works proposed a technique for predicting the full trajectory of brain shape changes as MCI progresses towards AD, remains stable, or reverses to normal.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the absence of network-based predictive models is remarkable (Table 1). As such, the use of advanced network and shape analysis methods, using machine learning, could prove fruitful for both classification [47,48,49,50] and prediction tasks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected 30 papers from the Medical Image Computing and Computer Assisted Intervention conference (MICCAI), the Information Processing in Medical Imaging (IPMI) conference, Journal of Neuroscience Methods, IEEE Transactions on Medical Imaging journal, Frontiers in Neuroscience, Neuroimage, Cerebral Cortex journals and bioRxiv. Non-GNN based papers related to brain graphs were excluded from our review such as those proposing CNN-based architectures for a connectomic related task or ML-based works such as (33,34,29). We refer the reader to our GitHub link where all papers cited in our work are available at https://github.com/basiralab/GNNs-in-Network-Neuroscience.…”
Section: Literature Search and Taxonomy Definitionmentioning
confidence: 99%
“…To address the limitation of conventional low-order brain network representation, recent pioneering works [5,6] introduced the concept of a brain multiplex, which in its shallow form, is composed of a source network intra-layer, a target intra-layer, and a convolutional inter-layer capturing the high-order relationship between both intra-layers. Basically, a brain multiplex can be viewed as a tensor stacking two brain networks (also called intra-layers) and one inter-layer that encodes the similarity between these two intra-layers.…”
Section: Introductionmentioning
confidence: 99%